Nanoporous Polymer Microspheres with Nitrile and Amidoxime Functionalities for Gas Capture and Precious Metal Recovery from E-Waste - Dogan, Nesibe A.; Hong, Yeongran; Özdemir, Ercan; Yavuz, Cafer T. (Amer Chemical Soc, 2019)
Nanoporous materials could offer sustainable solutions to gas capture and precious metal recovery from electronic waste. Despite this potential, few reports combine target functionalities with physical properties such as morphology control. Here, we report a nanoporous polymer with microspherical morphology that could selectively capture gold from a mixture of 15 common transition metals. When its nitriles are converted into amidoxime, the capacity increases more than 20-fold. Amidoximes are also very effective in CO2 binding and show a record high CO2/CH4 selectivity of 24 for potential use in natural gas sweetening. The polymer is successfully synthesized in 1 kg batches starting from sustainable inexpensive building blocks without the need for costly catalysts. Because the morphology is controlled from the beginning, the nanoporous materials studied in lab scale could easily be moved into respective industries.
Keywords: Porous polymers; Electronic waste treatment; Sustainable adsorbents; Hollow microspheres; Methane separation; Gold capture; Large scale synthesis